Penerapan Sistem Informasi Perpustakaan Berbasis Web Pada SDS prabhudy PWKI - Mahulae, Mayanti Astika; Marbun, Nasib (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
This research aims to develop a web-based library information system at Prabhudy Pwki Elementary School. Currently, SDS Prabhudy Pwki faces problems in managing library data using manual methods that are less effective and prone to errors in data processing, frequent data redundancies, and data loss. The method used to develop a web-based library information system in this research is the waterfall method. The tool used in building a web-based library information system in this study is the PHP programming language: Hypertext Preprocessor and MySQL database. The results of this study concluded that the web-based library information system developed in this study can solve the problems faced by the library staff at SDS Prabhudy Pwki when still using manual methods in managing book data, member data, book borrowing data, and book return data. In addition, this research is also expected to be an accurate reference for further researchers who discuss the development of web-based library information systems in other research sites..